Family businesses that produce counterfeits: what is stopping them from creating their own brand? - Khan, Tahsan Rahman (© 2012 The Authors. Published by Elsevier Ltd, 2016)
This article was published in Procedia Economics and Finance [© 2012 The Authors. Published by Elsevier Ltd] and the definite version is available at : http://ac.els-cdn.com/S2212567112003450/1-s2.0-S2212567112003450-main.pdf?_tid=23aa9c24-73ed-11e6-a1af-00000aacb35d&acdnat=1473137482_3e19ab4286fe899e128507bbac3cf2b1 The article website is at: http://www.sciencedirect.com/science/article/pii/S2212567112003450 DOI: 10.1016/S2212-5671(12)00345-0